1516. Evaluating Appropriate Antimicrobial Selection and Duration of Therapy for Urinary Tract Infections in Outpatient Clinics. (26th November 2018) - Green, Melanie; Nagel, Jerod; Petty, Lindsay
Abstract: Background: Each year in the United States, ~97 million outpatient visits result in the prescription of an antibiotic. However, there is limited data describing prescribing practices for urinary tract infections (UTIs) in outpatient clinics. We aimed to describe the prescribing patterns for UTIs among varied provider groups and clinic subspecialties, in order to improve targeted interventions to improve antibiotic use. Methods: This retrospective study included patients from January 2016 through December 2016 within a large academic healthcare system presenting to 30 clinics, including family medicine, general medicine, urology, geriatric, and OB/GYN. Patients were included if they had a diagnosis of a lower tract UTI (ICD-10 codes for acute cystitis (N30) and cystitis with or without hematuria (N30.90–91). Exclusions included pregnancy, prophylaxis prior to urology procedure, antibiotics not prescribed, or antibiotic prophylaxis. Patients were categorized as complicated vs. uncomplicated based on additional ICD-10 codes for uncontrolled diabetes, urinary obstruction, flank pain, renal failure, gender, and receiving immunosuppression. Additionally, patient allergies were evaluated to assess adherence to guidelines (Figure 1). The primary objective was to describe prescriber compliance with institutional UTI guidelines for both drug selection and duration. Results: From 30 clinics, 1, 488 patient encounters for UTI were included. The overall compliance rate was 9.5% for appropriate drug selection and duration of therapy, with appropriate drug selection (22.8%) being much lower than appropriate duration (84.9%). The most commonly prescribed antibiotics included trimethoprim/sulfamethoxazole (31.8%), FQs (23.2%) and nitrofurantoin (21.7%). Compliance rates varied widely between prescriber types (Figure 2). Conclusion: Management of UTIs in outpatient clinics is suboptimal, and would benefit from antimicrobial stewardship interventions. Stewardship efforts in outpatient clinics should target both appropriate drug selection and duration, and de-emphasize FQ use. Disclosures: All authors: No reported disclosures.